Should psychosocial intervention be added to pharmacological treatment for opiate abuse/dependence? An overview of systematic reviews of the literature (Italian Journal of Public Health, 2006)
Background: Opioid abuse and dependence are major health and social issues in most societies. Differentinterventions are available, but the majority of heroin patients relapse and these relapses are a substantialproblem to their rehabilitation. Psychosocial interventions for drug addicts have been suggested as possibleinstruments to overcome the difficulty of maintaining a drug-free state. The aim of this paper is to provide asummary of the available evidence of effectiveness.Methods: We summarised the results from two systematic reviews on psychosocial interventions combinedwith Methadone Maintenance Treatment and Methadone or Buprenorphine Detoxification Treatment. Results:For detoxification treatments, the results show that benefits can be gained from adding any psychosocialtreatment to any substitution detoxification treatment in terms of completion of treatment: relative risk (RR)1.68 (95% CI 1.11-2.55), and compliance (proportion of clinical absences): RR 0.48 (95% CI 0.38-0.59); for theuse of heroin during treatment, the differences were not statistically significant. For maintenance treatments,there is an additional benefit to be gained in adding any psychosocial treatment to methadone maintenancetreatment in relation to the use of heroin during treatment: RR 0.69(95% CI 0.53-0.91); no statisticallysignificant additional benefit was shown in terms of treatment retention and results at follow-up.Conclusions: Psychosocial treatments offered in addition to pharmacological detoxification treatments areeffective in terms of completion of treatment and compliance, while adding any psychosocial support tomethadone maintenance significantly improves the non-use of heroin during treatment but does not improvethe other outcomes considered
Keywords: opioid-related disorders; methadone; buprenorphine; systematic review